MODEL BERCERITA UNTUK MENINGKATKAN KECERDASAN ANAK: APLIKASI ANCANGAN PSIKOLINGUISTIK - . Subiyantoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
The research aims at obtaining a model of story-telling based on the analysis of the functions of characters in children story that can improve the emotional quotient. This study on emotional quotient used the framework of research development. As a result, emotional quotient can be developed which can be shown by the tendency of the improvement of the emotional quotient of the children under study. This was proved by the changing of the emotional quotient of those children.